Rook's Textbook of Dermatology, Ninth Edition 2016
DOI: 10.1002/9781118441213.rtd0156
|View full text |Cite
|
Sign up to set email alerts
|

Skin Ageing

Dana L. Sachs,
Gary Fisher,
John J. Voorhees

Abstract: Skin ageing results from both the passage of time and from extrinsic forces, predominantly solar ultraviolet irradiation. Intrinsic ageing is characterized by fine wrinkling and homogenous colour on sun‐protected sites whereas extrinsic ageing is characterized by fine and coarse wrinkling, erythema and dyspigmentation on sun‐exposed sites. Two distinct phenotypes of extrinsic ageing have emerged: atrophic and hypertrophic variants. Tools to measure and quantify skin ageing have been developed and offer therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 97 publications
0
0
0
Order By: Relevance
“…Different anti-aging approaches have been developed to rejuvenate aged skin and prevent age-related skin diseases. Among anti-aging substances, retinoids and alpha-hydroxy acids are the actives commonly used at the topical level [7] and retinoic acid represents the gold standard treatment [3]. Retinoic acid and its metabolic precursor, retinol, increase collagen formation, preventing collagen degradation in the skin and leading to a clinical improvement in wrinkles.…”
Section: Topical Retinoids and Skin Agingmentioning
confidence: 99%
See 3 more Smart Citations
“…Different anti-aging approaches have been developed to rejuvenate aged skin and prevent age-related skin diseases. Among anti-aging substances, retinoids and alpha-hydroxy acids are the actives commonly used at the topical level [7] and retinoic acid represents the gold standard treatment [3]. Retinoic acid and its metabolic precursor, retinol, increase collagen formation, preventing collagen degradation in the skin and leading to a clinical improvement in wrinkles.…”
Section: Topical Retinoids and Skin Agingmentioning
confidence: 99%
“…Retinoic acid and its metabolic precursor, retinol, increase collagen formation, preventing collagen degradation in the skin and leading to a clinical improvement in wrinkles. In addition, retinoic acid also determined an improvement in dyspigmentation [3]. Recently, a clinical trial showed the clinical efficacy and tolerability of a medical device containing retinoic acid (0.02%) and glycolic acid (4%) in a polyvinyl gel vehicle (RG) [7] as an anti-skin aging strategy.…”
Section: Topical Retinoids and Skin Agingmentioning
confidence: 99%
See 2 more Smart Citations